Antenna surface plasmon emission by inelastic tunneling - Cheng Zhang (Nature Portfolio, 2019)
Developing a microscale ultrafast electrical source of surface plasmons is crucial for nanophotonic applications. Here, the authors report the design, fabrication and characterization of nanoantennas for emission and control of surface plasmons by inelastic electron tunneling.